Penguatan Literasi Digital Melalui Pelatihan Menggunakan Media Pembelajaran Virtual Reality Bagi Guru SMK - Hendra Jaya; Sapto Haryoko; Mantasia Mantasia; Putri Ida Sunaryati; Sutarsi Suhaeb (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
The aim of this activity is to find out the problems of the complete systematic land registration program at the Gorontalo Regency Land Agency and efforts to resolve them. The method used is law with an empirical approach, which presents data according to field facts which are then analyzed descriptively qualitatively. The results of the research show that in land registration through the PTSL program there were problems such as a lawsuit for a certificate from the actual owner, where when the PTSL implementation was completed by the village and land agency and a certificate of ownership was issued to those who applied, it turned out that it was suddenly protested by the community who claimed to be the real owner and this happens especially on land abandoned by the previous owner (abandoned); Low public understanding of land tenure law where not all people understand PTSL procedures, so there is still public distrust in making certificates which are considered complicated and take a long time; There are public perceptions regarding the high cost of obtaining certificates, including concerns that they will be burdened by the increasing tax value; and the lack of human resources, especially skilled personnel in villages and BPN in handling land conflict matters and cases. Efforts to resolve this problem are to maximize socialization to the community regarding the terms and conditions and land registration procedures; clarify the status of the land you wish to certify so that it does not overlap; and re-preparing the land registration quota which is still lacking, meaning there is still land in villages in Gorontalo Regency that cannot be accommodated in the PTSL program, which is adjusted to the existing budget.